Praktik Etika Bisnis dakam Kegiatan Ekonomi Mikro Islam - Sania, Vera; Admaja, Yuda; Dalimunthe, Faisal Anwar (Jurnal Deflasi, 2025)
Business ethics plays an important role in ensuring fairness, transparency, and responsibility in economic activities, including in the Islamic economic system. This research aims to analyze the application of Islamic business ethics principles in economic transactions, such as honesty (sidq), justice ('adl), prohibition of usury (gharar), and mutually beneficial cooperation (ta'awun). The research method used is a literature study with a qualitative approach, examining primary sources such as the Qur'an, Hadith, and the opinions of scholars and practitioners of Islamic economics. The results show that the application of Islamic business ethics not only prevents harmful practices, but also creates trust and blessings in transactions. These principles are embodied in sharia contracts such as murabahah, mudharabah, and musyarakah, which emphasize justice and balance between the parties involved. The implication is that the integration of Islamic business ethics in economic transactions can encourage sustainable and equitable economic growth in accordance with maqashid sharia.